1997
DOI: 10.1016/s0735-1097(97)00029-6
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Microbubbles and Ultrasound: In Vitro and In Vivo Observations

Abstract: Ultrasound results in microbubble destruction that is more evident at lower frequencies and higher acoustic powers. Reducing the exposure of microbubbles to ultrasound minimizes their destruction. This effect is most marked in vivo with venous rather than aortic or direct coronary injections of microbubbles. These findings could lead to effective strategies for myocardial perfusion imaging with venous injections of microbubbles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
133
2
5

Year Published

1997
1997
2006
2006

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 278 publications
(142 citation statements)
references
References 16 publications
2
133
2
5
Order By: Relevance
“…107 Microbubbles, by acting as cavitation nuclei, may potentiate pore formation in cell membranes, thus facilitating the entry of plasmids into cells and their release from endosomes. 113 Our Figure 4 Schematic diagram of the proposed routes by which naked plasmid DNA is delivered to muscle fibres and transgene products are secreted into circulation. The route of endocytosis (a) is exemplified by lipoplex-mediated plasmid delivery whereas the route of passive entry (b) is by electroporation.…”
Section: Microbubbles and Ultrasoundmentioning
confidence: 99%
“…107 Microbubbles, by acting as cavitation nuclei, may potentiate pore formation in cell membranes, thus facilitating the entry of plasmids into cells and their release from endosomes. 113 Our Figure 4 Schematic diagram of the proposed routes by which naked plasmid DNA is delivered to muscle fibres and transgene products are secreted into circulation. The route of endocytosis (a) is exemplified by lipoplex-mediated plasmid delivery whereas the route of passive entry (b) is by electroporation.…”
Section: Microbubbles and Ultrasoundmentioning
confidence: 99%
“…[4][5][6][7][8] We have recently shown that exposure of microbubbles to ultrasound results in their destruction. 9 This effect could be related to the induction of nonlinear oscillations in the microbubbles or represent a nonspecific effect related to the acoustic power. Regardless of the exact mechanism of ultra-sound-induced microbubble destruction, the acoustic emissions from oscillating or imploding microbubbles contain harmonics of the frequency to which the bubbles were initially exposed.…”
mentioning
confidence: 99%
“…10,11 Because harmonic signals emanate mostly from bubbles rather than tissue, selective reception of these signals results in an increased signal-to-noise ratio. 4,5,9,12 For this study, we hypothesized that ultrasound-induced destruction of intravenously delivered bubbles can be used to quantify myocardial perfusion. If microbubbles are administered as a continuous infusion, then their destruction within the myocardium and measurement of their reappearance rate will provide a measure of mean myocardial microbubble velocity.…”
mentioning
confidence: 99%
“…12,13 However, clinical application of MCE requires extensive expertise in imaging techniques and accurate image interpretation because there are multiple variables and artifacts that affect adequate imaging and interpretation of myocardial perfusion. [12][13][14][15][16] In this study, by using a continuous infusion of PESDA, images could be repeatedly obtained and optimized by minimizing motion or blooming artifacts, and the transducer position was adjusted to move the lateral or inferior wall toward the center of the sector. To differentiate true perfusion defects from artifacts, we systematically changed the triggering interval from 1:1 to 1:5 to 1:10, analyzed patterns of defects, and interpreted defects in the context of regional wall motion.…”
Section: Myocardial Contrast Echocardiographymentioning
confidence: 99%